O Tribunal de Contas e a sociedade em rede : uma nova dimensão para o controle social - Fonsêca, Rafael Sousa (2018)
The present work will deal with the constitutionalisation of the right to exercise social control and the duty of a positive action of the State for its effectiveness, since it is a right of second dimension. For the realization of this right, the right of access to information and the principle of transparency must be guaranteed. Among the subjects forced to foment and achieve social control, are the Courts of Accounts. They must act in order to realize this right, so it must provide a channel of interaction between the citizens and the Courts; keep the data to be audited in intelligible language, immediately and condensed; and make pedagogical content accessible. One way to implement the interaction between the Courts and the population, respecting the requirements, is the use of information technologies, that is, the set of activities provided by computing resources that aim at information production and transmission. They are essential for strengthening connectivity. Thus, in the network society, these networks should function as appropriate instruments for the effective control of communication between the interactive society and the Audit Courts, insofar as these bodies are specialized in overseeing the regularity of the State's financial activity. The problem is to verify whether the Audit Courts have used information technology as a tool to facilitate social control. The general objective is to demonstrate that the improvement of the use of information technologies in the current social and economic context, in the terms established by Castells, represents a necessary variable for social control and for the improvement of the external control performed by the Cortes de Contas. The present study shows that the hermetic and bureaucratic structure of the Courts of Accounts is not compatible with the openness and connectivity provided by the current social and state morphology, namely, an information society, consisting of networks, and a Digital Government. We used the deductive method and as research sources the bibliographic review on the subject and related legislation. Quantitative and qualitative data will be analyzed from the Brazilian Audit Courts and the Supreme Audit Institutions of Latin America.